Annual Plan 1995-96 Volume-I Introduction and General Statements - Planning Commission (Planning Commission, 1995)
With the re-organisation of the North East in the early 70's, the State of Meghalaya came into existence on 21 January 1972. Till then, the erritories, now forming the Stale of Meghalaya, were a part of the Slate of Assam. the former United Khasi and Jaintia Hills and Garo Hills Districts of Assam had earlier been constituted as an autonomous Stale in 1970. The pull-fledged Slate of Meghalaya has now completed over two decades of Planned efforts towards economic development and social change. 2. One of the smallest States in the Indian Union, Meghalaya has area of 22,500 sq. kms. and a population of little over 1.77 million. The State borders on Bangladesh on the southern side for over 496 Kms. and it is surrounded by Assam on all other sides.
Planning Department Government of Meghalaya